Eurasian otter Lutra lutra in developing countries: a resurvey of Albania 22 years after the fall of communism. Issue 2 (11th February 2015) - Balestrieri, Alessandro; Messina, Simone; Pella, Francesca; Prigioni, Claudio; Saino, Nicola; Fasola, Mauro
Abstract: In countries with emerging and developing economies the need to promote development and the lack of information on the status of the Near Threatened Eurasian otter Lutra lutra have given rise for concern about the conservation status of the species. In Albania information about the distribution of this otter dates from 1985. In 2013 we resurveyed 31 sites previously surveyed in 1985, and a further 42 sites throughout the country. At each site nine habitat variables of potential importance to otters were recorded and analysed. Overall the distribution pattern in 2013 did not differ from that recorded in 1985, although a reduction in marking intensity suggested a possible decline in otter numbers. Distribution of the otter has been influenced by land use and human density, suggesting man-induced habitat changes since the fall of communism may have affected the quality and fragmentation of otter habitats.